2019
DOI: 10.1101/515296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Toxoplasma Vacuolar H+-ATPase regulates intracellular pH, and impacts the maturation of essential secretory proteins

Abstract: Running title: Toxoplasma V-H + -ATPase 2 HIGHLIGHTS • The V-H + -ATPase localizes to the plasma membrane and pumps protons outside the cell • The V-H + -ATPase localizes to pro-rhoptries in dividing parasites and to the plant-like vacuole in extracellular tachyzoites. • The Vacuolar-H + -ATPase supports the maturation of rhoptry and microneme proteins. • Loss of V-H + -ATPase activity leads to hyperaccumulation of immature rhoptry and microneme proteins and defective microneme distribution and secretion. SUMM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 63 publications
0
30
1
Order By: Relevance
“…Genetic disruption or chemical inhibition of these maturases lead to severe blocks in invasion and egress (Nasamu et al., 2017; Pino et al., 2017). Of relevance, parasite depleted in vacuolar‐proton ATPases (V‐H+‐ATPases) exhibited a delay in ASP3‐dependent maturation and defective rhoptry function (Stasic et al., 2019), probably due to the absence of proper pre‐rhoptry acidification (Yakubu et al., 2018) needed for protease activity and condensation of the organelle content. Another class of proteins has been recently described as being important for secretory organelles maturation and morphology.…”
Section: Rhoptry Organelle Biogenesismentioning
confidence: 99%
“…Genetic disruption or chemical inhibition of these maturases lead to severe blocks in invasion and egress (Nasamu et al., 2017; Pino et al., 2017). Of relevance, parasite depleted in vacuolar‐proton ATPases (V‐H+‐ATPases) exhibited a delay in ASP3‐dependent maturation and defective rhoptry function (Stasic et al., 2019), probably due to the absence of proper pre‐rhoptry acidification (Yakubu et al., 2018) needed for protease activity and condensation of the organelle content. Another class of proteins has been recently described as being important for secretory organelles maturation and morphology.…”
Section: Rhoptry Organelle Biogenesismentioning
confidence: 99%
“…Despite its importance, the VAC has not been well characterized. Only a few proteins have been localized to the VAC/PLV [4,10,1417]. The VAC exists as a prominent intact organelle during initial infection and subsequently fragments during intracellular replication, based on staining of TgCPL, a major luminal protease in the VAC [4].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that proton transport at the plasma membrane regulates Ca 2+ influx, possibly by controlling the parasite plasma membrane potential (Stasic et al., 2019) or by coupling H + ejection with Ca 2+ influx (Schwiening et al., 1993b) by the plasma membrane Ca 2+ /H + counter‐transporting ATPase TgA1 (Luo et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work localized the V‐ATPase to the plasma membrane, PLV, and immature rhoptries of T. gondii (Stasic et al., 2019). Additional vesicles were also observed that were not identified.…”
Section: Discussionmentioning
confidence: 99%